Modelling of Cold Heavy Oil Production with Sand (CHOPS) using a fluidized sand algorithm - Haddad, Amin Sharifi; Gates, Ian (Fuel (Guildford), 2015)
•Cold Heavy Oil Production with Sand (CHOPS) is a non-thermal oil recovery method.•Sand production creates high permeability channels (wormholes) for heavy oil flow.•Minimum fluidization velocity concept used to model the CHOPS process.•Model robustly matches CHOPS field operations in multiple wells.•Dynamic growth of wormholes and dilation effects around them control production. Cold production has been established as a key recovery process used to recover viscous oil from Western Canadian Sedimentary Basin (WCSB) heavy oil reservoirs. Field production has demonstrated that aggressive sand production improves the recovery performance leading to the Cold Heavy Oil Production with Sand (CHOPS) process. The produced sand volume is speculated to produce wormholes – depleted high permeability sand channels within the heavy oil reservoir. Extensive laboratory experiments, field tracer tests and modelling of CHOPS have demonstrated that high permeability channels are formed but as yet, the mechanisms of the initiation and growth of wormholes remain unclear. These processes are effective for producing fossil fuels, in the form of heavy oil, because they are primary production processes with small amounts of energy used to produce the oil. In this study, we use the minimum fluidization velocity concept to model the CHOPS process in a heavy oil field located in the Cold Lake area. In this model, wormhole growth evolves in the reservoir considering foamy oil flow, sand fluidization, and sand production. The results demonstrate that the model provides a reasonable and robust representation of the production process.